Use of lightweight FFT-based algorithms for remote measurements using DIC - Slávek Zbirovský; Václav Nežerka (Acta Polytechnica CTU Proceedings, 2023)
Abrupt collapse events that result in casualties due to failure of load-bearing structures have been reported in recent years. Continuous remote monitoring of these structures, assessing the behavior under operational load, could provide a reliable prevention, as the developing damage manifests itself through a loss of stiffness, and therefore excessive deflections. Digital image correlation (DIC) algorithms based on fast Fourier transform (FFT) were implemented in a small computer unit Raspberry Pi, capable of remote operation in a low-energy demand mode. The unit is fully autonomous, capable of localizing QR code targets and extracting encoded information. This strategy allows us to instantly evaluate displacements of QR codes attached to any surface and send the data to a server. The software was developed in Python, allowing for two modes: the online mode for current data evaluation with information transfer via the MQTT protocol and the offline mode used for retrospective evaluation.